Intercalation of urea between kaolinite nanolayers for controlled release fertilizer application - Mahdavi, Fariba (2012)
In this study the high surface area of kaolinite nanolayers was exploited as a reservoir of urea in order to minimize nitrogen leaching, to prepare controlled release fertilizer (CRF). Urea was intercalated between kaolinite nanolayers through three different methods including ultrasonication as well as wet and dry grinding. For each technique, the effect of several parameters including urea concentration, time of process and temperature on the degree of intercalation was studied individually. The results of X-ray diffraction (XRD) showed that among these factors, urea concentration was effective and the interlayer spacing of kaolinite expanded from 7.1 Å to 10.9 Å for the highest urea concentration (urea/kaolinite=8/1). Complete intercalation which was calculated using intercalation ratio formula was achieved using dry grinding method. The morphology of kaolinite before and after intercalation was studied by using field emission scanning electron microscopy (FESEM). Also, Fourier Transform Infrared Spectroscopy (FTIR) revealed hydrogen bonding between kaolinite and urea. The thermal behavior of intercalated kaolinite was investigated using thermogravimetric analysis (TGA) and the CHNS elemental analyzer determined that 20 wt.% urea was loaded within the kaolinite surface. To prepare nitrogen-based CRF (NCRF), urea-intercalated kaolinite was mixed with aqueous solution of hydroxypropyl methylcellulose (HPMC) as the binder and then was granulated in three different sizes and coated with three different ter-based polymer coatings including water based epoxy resin, water-based thermoplastic acrylic resin, and, water based thermosetting acrylic resin. The granules were incubated in water at room temperature for 30 days and the urea release was measured in 5 days interval using UV/Vis technique and through diacetylmonoxime (DAM) colorimetric method. The effect of several factors including binder concentration, size of granules, coating thickness and the water absorbency of coating on urea release behavior of the NCRFs was investigated. The urea release from the coated NCRFs was evaluated according to the standard declaration of CRFs and was compared with the release properties of non-coated NCRF granules, with the non-intercalated kaolinite-urea granules and with the release behavior of conventional urea granules. From the UV/Vis results, binder concentration was not effective on the release behavior of the NCRF. On the other hand, the results showed that by increasing the thickness of coating and the size of granules the percentage of urea release decreased. The NCRFs with the largest size and the highest coating thickness coated with the thermoplastic acrylic resin had the lowest ratio of nitrogen release among all samples. Also, the controlled release properties of the NCRFs revealed that the standard of controlled release fertilizer was conformed to.